Optimal configuration method of distributed generation considering flexible distribution unit - YANG Xiaohui; YANG Shuang; XU Zhenghong; ZHANG Liufang; YANG Chunsheng (电力工程技术, 2023)
The unreasonable planning of the access location and capacity of distributed generation (DG) affects the distribution network. The flexible power distribution unit has the advantages of flexible power flow distribution and voltage improvement. The steady-state calculation model and control strategy model of the flexible distribution unit are put forward. In order to locate and fix the capacity of DGs more reasonably, the comprehensive acceptance standard model of three indexes, namely life cycle cost (LCC), network loss and voltage deviation are established firstly. Then, the improved sparrow search algorithm (ISSA) is proposed to solve the model. Gaussian variation and Tent chaos are introduced to improve the global searching ability and convergence speed of the algorithm. Finally, the IEEE 33-node distribution system is taken as an example for simulation analysis. Considering the two cases of unconnected and connected flexible distribution unit respectively, particle swarm optimization (PSO) algorithm, sparrow search algorithm (SSA) and ISSA are used to solve the problem. The results show that the power flow of the system and the system operating status after the DGs are configured can be improved by taking into account the flexible distribution unit. And the optimization result of the ISSA is more efficient and accurate than the optimization results of other algorithms.